Effects of Bank Lending on Economic Growth in Nepal - Timsina, Neelam; Pradhan, Radhe Shyam (Journal of Advanced Academic Research, 2017)
This study examines the effects of commercial bank lending on economic growth in Nepal. The study has conducted correlation and regression analysis using panel data of twenty four commercial banks during the period of 1996 -2015. The empirical results show that bank lending has positive effects on the economic growth in Nepal. The study implies that the policy makers should focus their attention more on the development of formal sector financing, adequate development of modern banking sector, development of efficient financial market and infrastructures and establishment of interest sensitive investment environment to increase the bank lending which is instrumental to promote economic growth in Nepal. Journal of Advanced Academic Research Vol. 3, No.3, 2016, page:53-75